Игры: обучение, тренинг, досуг: сборник сценариев / под ред. В. В. Петрусинского (Новая школа, 1998)
Экземпляры: ЧЗ (20151211) / Инвентарный номер: 33402 / Цена: 46450.00 / Авт.знак: И 27 / ГРНТИ: 14 / ББК: 74.200.58